GAGURITAN NI CANDRAWATI: ANALISIS STRUKTUR DAN MAKNA - Ida Ayu Made Setya Pratiwi; Putu Sutama; I Nyoman Duana Sutika (STKIP Subang, 2026)
Gaguritan Ni Candrawati is one of the classical Balinese literary works composed in the form of pupuh Ginada consisting of 58 stanzas, transcribed by Wayan Budha Gautama in 1992. This study aims to describe the structure and meaning contained in Gaguritan Ni Candrawati. The research employed a qualitative method with a descriptive-analytic approach. Data were collected through reading and note-taking techniques (simak-catat), followed by literal and idiomatic translation. Data analysis used structural and semiotic theories. The results show that the formal structure of Gaguritan Ni Candrawati consists of literary and linguistic codes, language varieties (alus, madia, kasar), and figurative language including comparative, contrastive, and associative styles. The narrative structure covers incident, plot, characterization, setting, theme, and moral message. The content structure is divided into three parts: the opening (character introduction and initial conflict), the middle (main conflict), and the closing (resolution and suffering of the protagonist). The meanings identified include religious, moral, social, humanistic, loyalty and sacrifice, and power critique meanings. This work depicts the suffering of Ni Candrawati caused by conflict between divine will and human judgment, generating empathy and deeper understanding of life values.